Colorectal cancer: from pathogenesis to prevention? - Seitz, Helmut K.; Simanowski, Ulrich; Wright, Nicholas A.; Morson, B. C. (Springer Berlin Heidelberg Imprint: Springer, 1989)
The data available on colorectal carcinogenesis has grown to such an extent that a new, critical analysis has become necessary. This volume gives such a summary of recent knowledge on the epidemiology, etiology and pathogenesis of colorectal cancer. Each chapter is written by an outstanding expert in the field. Risk factors, such as genetic heritage and environment, and the role they play in carcinogenesis are discussed. The relationship between colorectal cancer and nutrition is examined in an attempt to determine detrimental dietary habits. The approach taken by the authors leads the way toward practical recommendations for cancer prevention